One-Way ANOVA - Weiss, David J (Analysis of Variance and Functional Measurement, 2005)
One-way ANOVA deals with the results of a straightforward experimental manipulation. There are several (two or more) groups of scores, with each group having been subjected to a different experimental treatment. The term one-way derives from the fact that the treatment for each group differs systematically from that for other groups in only one respect: that is, there is one independent variable. Within each group, the treatment should be identical for all members. Each score comes from a separate individual, or, stated otherwise, each individual contributes only one score. The traditional name for an individual furnishing a score is subject. In recent years, the more egalitarian term participant has come to be favored. The modern term connotes a voluntary contribution to the research, a partnership between investigator and investigatee. volunteer is another label used for this usually anonymous member of the research team. All of these terms will be employed in the text.